A Commentary on George Lakoff’s “Metaphors of Terror” - Roger S. Frantz (Studies in Applied Linguistics & TESOL, 2002)
The linguist Norman Fairclough (1992) argued that, in recent years, there has been a significant shift in the social functioning of language, a shift reflected in the salience of language in the major social changes which have been taking place over the last few decades. Many of these social changes do not just involve language, but are constituted to a significant extent by changes in language practices; and it is perhaps one indication of the growing importance of language in social and cultural change that attempts to engineer the direction of change increasingly include attempts to change language practices (p. 6). In short, language use and social change have become more intertwined and mutually constitutive in today’s world. This phenomenon presents linguists with an opportunity and a challenge. The opportunity is to bring an analytic understanding of language use to the public. The challenge lies both in the fact that linguists are not accustomed to communicating their understanding of language in a non-academic manner and the fact that the public is not naturally accustomed to thinking analytically and critically about language use.